2017
DOI: 10.3168/jds.2017-13054
|View full text |Cite
|
Sign up to set email alerts
|

A 100-Year Review: Metabolic health indicators and management of dairy cattle

Abstract: Our aim in this Journal of Dairy Science centennial review is to describe the evolution of focus on metabolic indicators, from discovery and description to evaluation at the individual cow and subsequently herd levels, over the past 100 yr. Furthermore, we discuss current and future technologies that will be used in the dairy industry to utilize these indicators widely going forward. Knowledge of chemical changes in various fluids (e.g., blood, urine, and milk) accompanying numerous metabolic disease states in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
104
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 161 publications
(176 reference statements)
3
104
2
2
Order By: Relevance
“…We observed that PA increased BHB concentrations during the first week after calving compared with CON. Plasma BHB concentrations of 10 to 14 mg/dL have been suggested as cut-off points for increased risk of metabolic disorders (Ospina et al, 2013;Overton et al, 2017). Furthermore, Ospina et al (2010) reported that cows with BHB concentrations >10 mg/dL between 3 and 14 d postpartum had >4 times higher risk of postpartum diseases (e.g., displaced abomasum, metritis, clinical ketosis) and were >15% less likely to be pregnant after the voluntary waiting period (by 70 d).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that PA increased BHB concentrations during the first week after calving compared with CON. Plasma BHB concentrations of 10 to 14 mg/dL have been suggested as cut-off points for increased risk of metabolic disorders (Ospina et al, 2013;Overton et al, 2017). Furthermore, Ospina et al (2010) reported that cows with BHB concentrations >10 mg/dL between 3 and 14 d postpartum had >4 times higher risk of postpartum diseases (e.g., displaced abomasum, metritis, clinical ketosis) and were >15% less likely to be pregnant after the voluntary waiting period (by 70 d).…”
Section: Discussionmentioning
confidence: 99%
“…They can be separated into 4 fractions by electrophoresis: α 1 -, α 2 -, β-, and γ-globulins (Busher, 1990). Physiological and pathological conditions can trigger changes in albumin and globulin concentrations (Alberghina et al, 2010;Overton et al, 2017), which can also be indicators of mammary gland inflammation (Bobbo et al, 2017a,b). In clinical practice, A:G may be useful in identifying endometritis and dysproteinemias (Kaneko et al, 2008;Overton et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The values found for nonesterified fatty acids reached 0.34 mmol/L. According to Overton [33], levels above 0.5 mmol/L in the prepartum period indicate a greater probability of developing some metabolic disease. Thus, the heifers in the present study with an average daily gain approximately of 1.0 kg are unlikely to present metabolic problems due to the low levels of β-hidroxibutirate and nonesterified fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the concentration of metabolites in dairy cows, studies using lactating cows have been carried out and limits of several metabolites have been established [33, 34, 35]. However, according to Briscic [36], reference values for heifers at the end of gestation have not been studied.…”
Section: Discussionmentioning
confidence: 99%